PENGARUH ARAH DAN UKURAN POTONGAN SISIK UMBI KERK LILY (Lilium longiflorum Thunb.) TERHADAP PEMBENTUKAN TUNAS MIKRO DAN BULBLET SECARA IN VITRO - Priyono, Priyono; Winarsih, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Mass production by using micro propagation technique has an important role for Lilium longiflorum regarding that it can produce seedlings in relatively short time, disease free, and regularly time. Several factors affected the successful micro shoots and bulblets formation, i.e.medium, explant, and temperature. This research aimed to know the effect of direction and width of scale section on the multiplication of kerk lily in vitro.Research has been conducted in the Tissue Culture Laboratory of Indonesian Coffee and Cocoa Research Institute, Jember.The research was arranged in factorial completely randomised design, i.e.direction of scale section and width of scale section. Two levels of direction of scale section namely longitudinal and transversal and five levels of width of scale section namely 1, 4, 6, 8, and 10 mm.The results showed that scales are able to produce micro shoot only, bulblet only, or both micro shoot and bulblet.The number of micro shoots produced from longitudinal section are higher than those of produced from transversal section. Width of scale section affected micro shoots and bulblets production, which their correlations are quadratic.The trend of micro shoots production was contrary with bulblet production.